Impact of mask wearing during high-intensity exercise on post-exercise hemodynamics - Zeigler, Z.; Price, P.; Nowlen, M.; Heikka, L.; Larson, R.; Thomasson, S.; Acevedo, A. (Journal of Human Sport & Exercise, 2023)
Background Few studies examining face mask wearing during high-intensity interval exercise (HIE) have measured blood pressure (BP) and cardiac output (Q) during exercise and none have examined these variables post-exercise.